Financial reforms and governance and the crisis in research in public universities in Africa: A case of Uganda - Kabeba, Muriisa Roberts (Journal of Educational Administration and Policy Studies, 2010)
Since the 1980s, African countries including Uganda, have been implementing financial reforms with particular emphasis on spending on priority sectors. Higher education sector was not given priority. In this regard, there was a shift from funding higher education to funding primary education in the 1990s, the consequence of which was a decline in public funding for university education. The effect of this policy shift was for universities to look for alternative funding sources. Universities have turned to privatisation and commercialisation of academic programs so as to continue functioning. In spite of the decline in public funding for universities, there is observation that funding from the private sponsorship scheme has increased but there is no corresponding increase in research and publication. Instead universities have glossily lamented over the decline in public funding as affecting their performance in areas of research and publication. There is little regard of the increased private and donor funding which could also contribute to research. In this paper, I argue that the financial governance and reforms rather than declining funding account for the decline in research in public universities in Uganda. The discussion presented will show that there is limited funding allocated to research resulting into low morale for research, and where research is done, there is more emphasis on applied research than basic research. In the last part of the paper I look at how universities can respond to the crisis of research by taking care of financial governance issues.
Keywords: Accountability; Transparency; Financial reforms; Financial governance